This preview shows pages 1–4. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: University of Ottawa MAT 1330D Midterm Exam March 18, 2009. Duration: 80 minutes. Instructor: Pawel Lorek SOLUTIONS of ver. A 1 ver. A Question 1. [4p] Use Newton’s method to find an approximation of the equilibrium of the following DTDS: x t +1 = h ( x t ) = x 2 t + 4 x t − 8 x t Use x = 2 and make at least two iterations (i.e. calculate x 2 ) Solution: We have to solve the following equation: h ( x ∗ ) = x ∗ ( x ∗ ) 2 + 4 x ∗ − 8 x ∗ = x ( x ∗ ) 2 + 3 x ∗ − 8 x ∗ = 0 It means we have to solve the following equation: f ( x ) = x 2 + 3 x − 8 x = 0 . We have f ′ ( x ) = 2 x + 3 − 8 · − 1 x 2 = 2 x + 3 + 8 x 2 . Therefore, the Newton’s method discretetime dynamical system is: x t +1 = x t − f ( x t ) f ′ ( x t ) = x t − x 2 t + 3 x t − 8 x t 2 x + 3 + 8 x 2 t We start with x = 2. x 1 = x − x 2 + 3 x − 8 x 2 x + 3 + 8 x 2 = 2 − 2 2 + 3 · 2 − 8 2 2 · 2 + 3 + 8 2 2 = 2 − 4 + 8 − 4 4 + 3 + 2 = 2 − 6 9 = 2 − 2 3 = 4 3 x 2 = x 1 − x 2 1 + 3 x 1 − 8 x 1 2 x 1 + 3 + 8 x 2 1 = 4 3 − ( 4 3 ) 2 + 3 · 4 3 − 8 4 3 2 · 4 3 + 3 + 8 ( 4 3 ) 2 = 4 3 − 16 9 + 4 − 8 · 3 4 8 3 + 3 + 8 · 9 16 = 4 3 − 16 9 + 4 − 6 8 3 + 3 + 9 2 = 4 3 − 16+36 − 6 · 9 9 16+18+27 6 = 4 3 − − 2 9 · 6 61 = 4 3 + 4 183 = 248 183 = 1 . 355191257 (calculator could be used to calculate above numbers faster) 2 ver. A Question 2. [5 points] Consider the function f ( x ) = 1 √ x (a) [2 points] Find the tangent line approximation with base point a = 1 . (b) [2 points] Find the Taylor polynomial of degree three with base point a = 1 . (c) [1 point] Calculate approximation of 1 √ 1 . 1 with the approximation from the tangent line and from the Taylor polynomial of degree 3 (found in (a) and (b)) Solution: Let’s recall the taylor polynomial matching n first derivatives at x = a : P n ( x ) = f ( a ) + f ′ ( a )( x − a ) + f ′′ ( a ) 2 ( x − a ) 2 + f (3) ( a ) 3! ( x − a ) 3 + ... + f ( n ) ( a ) n ! ( x − a ) n , where f ( k ) denotes k − th derivative of f . For simplicity let’s write: f ( x ) = x − 1 2 . We will also need the following: f ′ ( x ) = − 1 2 x 3 2 f ′′ ( x ) = − 1 2 · ( − 3 2 ) x 5 2 = 3 4 x − 5 2 f ′′′ ( x ) = 3 4 · ( − 5 2 ) x − 7 2 = − 15 8 and f (1) = 1 , f ′ (1) = − 1 2 , f ′′ (1) = 3 4 , f ′′′...
View
Full
Document
This note was uploaded on 01/16/2011 for the course MAT 1330 taught by Professor Dumitriscu during the Fall '08 term at University of Ottawa.
 Fall '08
 DUMITRISCU
 Calculus, Approximation

Click to edit the document details